Studi Eksperimental Deformasi Kristal Pada Daerah Haz Dengan Menggunakan Xrd Dan Metode Scherrer (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2017)
The welding process as technology that commonly is used to join some part become the engine frame. The correct parameter can avoid the welding defect on the weld result, i.e. the welding of AISI 1045. The study of welding deformation is needed to avoid the weld result from the welding defect.The welding current and the plat thickness are as the research parameter. As the welding tool is used GMAW that manually operated. An electrode type AWS A/SFA 5.18ER. 70S-6 as the welding electrode. The welding current are 175 A, 225 A and 275 A. The crystallic structure are analysed by using X-Ray Deffractrometer and Scherrer methods are used to know the crystallic development as the weld current and the cooling rate as dimensional effect. The result of metal structure at XRD test are showed increased about the peak of X-Ray wave about 25 % at the base metal, 30 % at the HAZ and 40 % at the weld metal that are seen from the wave reflection of X-Ray. The maching result by using JCPDS is 750910. The nearest spread angle about 2 = 44,713, the X-ray intensity about 338, at hkl plane (022) as Fe3C has orthorhombic structure with a = 4,518 Å, b = 5,069 Å dan c = 6,736 Å. Keyword : HAZ, crystallics structure, XRD, JCPDS.